Evaluation of Waiting Time for Recipe Services at Puskesmas Mangunjaya Based on Ministry of Health Regulation - Permana, Kusyana Ade; Ismail, Rian; Wahlanto, Panji (LPPM STIKes Muhammadiyah Ciamis, 2024)
Pharmaceutical services include resource management consisting of resources Humans, facilities, pharmaceutical preparations and health supplies as well as Administration and Pharmacy Services Clinical in efforts to achieve the stated goals. Prescription services are one of aspect clinical pharmacy services which include receiving prescriptions, assessment prescription administration, pharmaceutical suitability, drug compounding and packaging as well delivery of medication to patients. The aim of this research is to find out the waiting time for prescription services at the Mangunjaya Health Care Center (Puskesmas Mangunjaya) Pangandaran based on health minister regulations. The results of the research conducted from concoction recipes as many as 4 samples and no-concoction of 186 samples, waiting time Recipe and Non-concoction prescription services meet the standards, average Recipe Services concoction 14.86 minutes and average non -concoction recipe services 2.42 minutes. It can be concluded that prescription drugs are concoction and non The concoction at the Mangunjaya Health Center meets the minimum service standards in accordance with the Ministry of Health Regulation No.129/Menkes/SK/II/2008.